Quantitative aspects of brain perfusion dynamic induced by BOLD fMRI Aspectos quantitativos da dinâmica perfusional do cérebro induzida pelo BOLD fMRI - Katia C. Andrade; Octavio M. Pontes-Neto; Joao P. Leite; Antonio Carlos Santos; Oswaldo Baffa; Draulio B. de Araujo (Arquivos de Neuro-Psiquiatria)
The increase of relative cerebral blood flow (rCBF) may contribute for a change in blood oxygenation level dependent signal (BOLD). The main purpose of this study is to investigate some aspects of perfusional alterations in the human brain in response to a uniform stimulation: hypercapnia induced by breath holding. It was observed that the BOLD signal increased globally during hypercapnia and that it is correlated with the time of breath holding. This signal increase shows a clear distinction between gray and white matter, being greater in the grey matter. O aumento relativo do fluxo cerebral sangüíneo (relative Cerebral Blood Flow - rCBF) pode contribuir para uma mudança no sinal dependente da oxigenação do sangue (Blood Oxygenation Level Dependent - BOLD). O objetivo principal deste trabalho foi estudar alguns aspectos da alteração perfusional no cérebro humano em resposta a um estímulo uniforme: hipercapnia, causada por um estado de apnéia induzida. Foi observado um aumento global no sinal BOLD durante a hipercapnia. Este aumento é correlacionado com a duração da apnéia e mostra uma clara distinção entre a substância branca e cinzenta, sendo maior na substância cinzenta.